Science in the School Program. (America Magazine: The Jesuit Review of Faith & Culture, 1916)
The article examines the complaint of a certain college professor concerning the lack of science education program in elementary schools in the U.S. According to the professor, science and literature should be included in the educational program. He observes that a typical modern school does not teach the children about science.